การพัฒนาวิธีการตรวจสอบรีคอมบิแนนต์ดีเอ็นเอในมะละกอและผลิตภัณฑ์มะละกอ - ปัทมา เสนทอง (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
For DNA extraction from fresh papaya and all texture of papaya processed products, protocol based on synthetic resin was more suitable than that using detergent of cetyl trimethyl ammonium bromide (CTAB). Further investigation on recombinant cassette of genes revealed the papain gene and its unique domain as an internal gene for 280 nt papain screening and the 800 nt of papaya ring spot virus coat protein gene as source for target recombinant DNA primer design. This covering all the permitted recombinant papaya events and the under developing transgenic papayas. It was found during condition determination that the suitable annealing temperature and magnesium concentration were at 52°C 2 min and 1.5 μmole respectively. The sensitivity for minimum papain and coat protein gene dosage for the test was 1.9635 μg/pl and 1.7538 μg/pl. And the liability based on reproducibility and specificity test was 99% and 100% respectively. For the test, reference positive control DNA was derived from a construction of plasmid DNA having an assemble of papain 358 promoter portion of papaya ring spot virus coat protein gene and terminator via PCR technique cloned into pCRll using TA cloning principle. This reference DNA could be detected even at concentration of 2.9634 pg/μl as low. The application of the method for papaya food testing revealed that among 3024 samples tested, all were papain positive and one as of imported product test positively with recombinant coat protein gene. The method constitutes a basis for assured testing on GMOs free papaya and their products for export.